Middle-Preserving Pancreatectomy for Multicentric Solid Pseudopapillary Neoplasm in a 10-Year-Old Female - Marshall, Grace; Byrne, Matthew; Wirth, Korry; Liao, Xiaoyan; Linehan, David C.; Wilson, Nicole A. (European Journal of Pediatric Surgery Reports, 2024)
Solid pseudopapillary neoplasm (SPN) is a rare low-grade malignant tumor of the pancreas that occurs predominantly in young females. This tumor is occasionally multicentric, posing a unique surgical conundrum for resection. We present a case of a 10-year-old female with a history of multicystic dysplastic left kidney and persistent urogenital sinus who was diagnosed with biopsy-proven multicentric SPN of the pancreatic head and tail and underwent middle-preserving pancreatectomy. The patient tolerated the surgery very well. Our case is one of the few reported cases of multicentric SPN in a pediatric patient, and the only case treated with middle-preserving pancreatectomy, which is a novel surgical option for protecting pediatric patients from total endocrine and exocrine pancreatic insufficiency. With the increase in the incidence of SPN, there is an increasing need for pancreas-preserving surgical options, particularly in pediatric patients.
Keywords: multicentric solid pseudopapillary neoplasm; Frantz tumor; urogenital abnormalities; pediatric; pancreas